Association between preoperative high-density lipoprotein cholesterol levels and overall survival in gastric cancer patients: a retrospective cohort study - Lei Ye; Yutong Zhang; Bin Ye; Qinghua Qi; Wenting Cao (BMJ Open, 2025)
Objectives This study aimed to evaluate the prognostic significance of preoperative serum lipid profiles, particularly high-density lipoprotein cholesterol (HDL-C), in gastric cancer (GC) patients undergoing gastrectomy.Design A hospital-based retrospective cohort study.Setting A tertiary hospital in Eastern China.Participants 771 consecutive GC patients who underwent gastrectomy between 2014 and 2018, had complete pathological data, and received standardised adjuvant chemotherapy (fluoropyrimidine or taxane-based regimens).Exposures Preoperative serum lipid profiles, including total cholesterol (TC), triglycerides (TG), HDL-C and low-density lipoprotein cholesterol (LDL-C), along with clinicopathological data, were collected. Patients were stratified by sex-specific lipid tertiles (T1–T3).Outcome measures The primary outcome was overall survival (OS), defined as the time from surgery to death from any cause or to the last follow-up. Secondary outcomes included stage-specific survival rate (stage III+IV versus stage I/II; M0 versus M1 status). Mortality HRs were estimated using Cox proportional hazards models: Model 1 adjusted for age and sex, and Model 2 fully adjusted for Tumor-Node-Metastasis (TNM) stage and tumour characteristics. OS was analysed using Kaplan-Meier curves and log-rank tests. Subgroup analyses were performed for variables with significant interactions.Results The cohort had a median follow-up of 41.0 months (range: 0.03–89.8 months), and an OS rate of 58.2%. In multivariable analysis, HDL-C was an independent prognostic factor (highest versus lowest tertile: HR 0.728 (95% CI 0.558 to 0.949), P-trend=0.019). The strongest associations were observed in the stage III+IV subgroup (HR 0.699 (95% CI 0.515 to 0.949), p-trend=0.021) and the M0 subgroup (HR 0.734 (95% CI 0.560 to 0.963), p-trend=0.025). After full adjustment, no significant associations were found for TG, TC or LDL-C.Conclusions Preoperative HDL-C predicted OS in GC patients, especially in those with locally advanced or non-metastatic patients. These findings suggest that lipid metabolism may affect tumour biology and prognosis in operable GC.